Hemispheric specialization and psychopathology - (:unkn) unknown (My University, 2001)
There are differences in the anatomy and functions of right and left cerebral hemispheres. The localization of a function on one side of the brain in preference to the other side is defined as lateralization. In general, it is suggested that the left hemisphere is analytic, the right is holistic, the left is verbal, and the right is perceptual. Linguistic abilities like grammar etc. are concentrated in the left hemisphere, but the right hemisphere also has a role in language and is important for timing and intonation. Right hemisphere is important in processing facial emotional input and it is more important than left in the expression of emotions. Studies on hemispheric determinants of behavior use various methods, among them are behavioral assessments on subjects with various localized brain damage including split-brain surgery, electrophysiological investigations as electroencephalography (EEG) and event-related potentials (ERPs), brain imaging studies as positron emission tomography (PET) and functional magnetic resonance imaging (fMRI), and divided visual field and dichotic listening experiments. Various studies on the relation of hemispheric specialization and psychopathology have been conducted to understand the neural mechanisms of mental disorders. In general, researches suggest that the key anatomical change in schizophrenia is a loss or even a reversal of cerebral asymmetry. The failure to develop normal cerebral asymmetry is suggested to be an important component of the underlying pathology in some forms of schizophrenia. Most of the other psychopathological conditions show varying degrees of lateralization. Emergence of new technological opportunities like transcranial magnetic stimulation (TMS) to effect one side of the brain encourages further studies on the role of lateralization in psychopathology.
Keywords: Lateralization; Mental disorder; Neurobiology